Analisis Faktor-Faktor yang Memengaruhi Perilaku Pengguna Sistem Informasi Akademik Mahasiswa dalam Penciptaan Kata Sandi Kuat dengan Menggunakan Protection Motivation Theory (Studi pada XYZ) - Yustiyana April Lia Sari; Ari Kusyanti; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Sistem Informasi Akademik Mahasiswa (SIAM) is a web-based Information Technology service that provides academic information services for students. The password policy service requires all students to create strong passwords in accordance with the policy for the creation of data security as well as user information. The user's desire to create a strong password is certainly influenced by several factors. The purpose of this study is to determine the factors that affect the user behavior of XYZ's SIAM account in the creation of strong passwords. This study uses Protection Motivation Theory (PMT) and is confirmatory because it only performs model testing based on previous research. Data collected from active users of SIAM service of XYZ were 281 respondents. Data analysis method used is Structural Equation Modeling (SEM) analysis. The research used six latent variables: Perceived Severity (PS), Perceived Vulnerability (PV), Fear (FR), Response Cost (RC), Response Efficacy (RE), and Intention (INT). From the research results, the factors that influence users in creating strong passwords according to policy are perceived vulnerability, response cost, and response efficacy.